2018
DOI: 10.1016/j.renene.2018.02.077
|View full text |Cite
|
Sign up to set email alerts
|

Air-cooled fuel cells: Keys to design and build the oxidant/cooling system

Abstract: In the field of energy, hydrogen as an energetic vector is becoming increasingly important. Specifically, fuel cells powered by hydrogen are becoming an alternative in automotive and other fields because of their ability to produce electricity without any pollution. Therefore, at this time there is a very active research field. A fuel cell can be described as a scale down industrial plant that consists of different subsystems whose purpose is to make the stack works properly. Air Cooled Polymer Electrolyte Fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…Therefore, additional air-cooling can be achieved by passing air through flow channels, e. g., by a fan. [154,155,156,157] As for the liquid cooling, the design of the flow channels also plays an important role for air-cooling. [158] Alternatively, reactant supply and cooling circuit can be combined in a so-called 'open-cathode' configuration.…”
Section: Thermal Management Of Pemfcsmentioning
confidence: 99%
“…Therefore, additional air-cooling can be achieved by passing air through flow channels, e. g., by a fan. [154,155,156,157] As for the liquid cooling, the design of the flow channels also plays an important role for air-cooling. [158] Alternatively, reactant supply and cooling circuit can be combined in a so-called 'open-cathode' configuration.…”
Section: Thermal Management Of Pemfcsmentioning
confidence: 99%
“…López-Sabirón et al 12 showed the infrared thermographic images of the surface of an air-forced open-cathode PEMFC stack. The work done by De las Heras et al 14 obtained infrared thermographic images of the surface of an air-forced open-cathode PEMFC stack. The study presented a brief temperature distribution of an air-forced open-cathode PEMFC stack; however, the temperature was not measured and analysed systematically.…”
Section: Introductionmentioning
confidence: 99%
“…The study presented a brief temperature distribution of an air-forced open-cathode PEMFC stack; however, the temperature was not measured and analysed systematically. The work done by De las Heras et al 14 obtained infrared thermographic images of the surface of an air-forced open-cathode PEMFC stack. They found that the maximum temperature difference was more significant with higher current.…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, en aplicaciones estacionarias, las pilas de combustible pueden conectarse a la red eléctrica (Moreira and da Silva, 2009), instalarse como generadores separados (Kirubakaran et al, 2009), u operar en vertederos y plantas de tratamiento de aguas residuales (Paska et al, 2009). Su uso también es interesante en aplicaciones de transporte, debido a la escasez de combustibles fósiles y sus escasos efectos contaminantes (Bertoluzzo and Buja, 2011;De las Heras et al, 2018b), o sobre otro tipo de estaciones móviles (Ross, 2003).…”
Section: Introductionunclassified